Implementation of Islamic Family Law on the Impact of Divorce on The Exercise of Child Custody and Education - Fikri Ahmad Ilhamdi; Emha Hasan Amiinulloh Asy’ari (al-Afkar, Journal For Islamic Studies, 2026)
Divorce not only raises legal issues between husband and wife but also affects child custody and education. This study examines the implementation of Islamic family law in child custody and education post-divorce, using a qualitative library-research approach with thematic analysis of regulations, court rulings, and relevant literature. The findings show that although the concept of hadhanah and national regulations provide detailed provisions on custody priority and maintenance obligations, implementation remains suboptimal: most fathers fail to fulfill maintenance obligations, leaving mothers to bear a dual role, while children face risks of psychological distress and declining academic performance. This gap mainly stems from weak enforcement and the dominance of cultural norms, although religious court mediation helps reduce conflict. The study underscores the need for an integrative approach combining regulatory strengthening, institutional capacity, and legal education.